Correcting the effect of stellar spots on ARIEL transmission spectra. Issue 2 (21st November 2020) - Cracchiolo, G; Micela, G; Peres, G
ABSTRACT: The goal of this study is to assess the impact of the stellar spots on the extraction of the planetary transmission spectra observed by ARIEL. We develop a method to model the stellar spectrum of a star in the presence of spots by using the out-of-transit observations. It is based on a chi squared minimization procedure of the out-of-transit spectrum on a grid of stellar spectra with different sizes and temperatures of the spots. The approach allows us also to study the temporal evolution of the spots when comparing stellar spectra observed at different epochs. We also present a method to correct the transit depth variations due to non-occulted stellar spots and estimate the error we introduce if we apply the same correction to crossings over the stellar spots. The method is tested on three types of stellar targets that ARIEL will observe in its 4-yr mission lifetime. In all the explored cases, the approach allows us to reliably recover the spot parameters (size and temperature) from out-of-transit observations and, for non-occulted spots, to confidently recover the planetary atmosphere transmission spectrum within the noise level (with average uncertainty of at most 3.3 per cent of the planetary signal). Conversely, we find systematic biases in the inferred planetary spectra due to the occulted spots, with measurable effects for the brightest targets especially for more contrasted spots.